2013
DOI: 10.1073/pnas.1306884110
|View full text |Cite
|
Sign up to set email alerts
|

Neurokinin3 receptor as a target to predict and improve learning and memory in the aged organism

Abstract: Impaired learning and memory performance is often found in aging as an early sign of dementia. It is associated with neuronal loss and reduced functioning of cholinergic networks. Here we present evidence that the neurokinin3 receptors (NK3-R) and their influence on acetylcholine (ACh) release may represent a crucial mechanism that underlies age-related deficits in learning and memory. Repeated pharmacological stimulation of NK3-R in aged rats was found to improve learning in the water maze and in object-place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 50 publications
(64 reference statements)
0
41
0
Order By: Relevance
“…An ideal animal model should exhibit all AD features in animals (Neha et al, 2014). Aging animals are commonly employed in AD drug development because they mimic not only the morphological characteristics (Erickson and Barnes, 2003;Gupta et al, 2013) but also the pathophysiology (de Souza Silva et al, 2013) of human Alzheimer's disease. Chronic administration of D-gal induces changes that resemble natural aging in rodents, including neurodegeneration (Ho et al, 2003;Zhang et al, 2005) and cognitive dysfunction (Cui et al, 2006;Wang et al, 2013), and thus becomes a routinely used method to induce aging in rodents (Wei al., 2005).…”
Section: Discussionmentioning
confidence: 99%
“…An ideal animal model should exhibit all AD features in animals (Neha et al, 2014). Aging animals are commonly employed in AD drug development because they mimic not only the morphological characteristics (Erickson and Barnes, 2003;Gupta et al, 2013) but also the pathophysiology (de Souza Silva et al, 2013) of human Alzheimer's disease. Chronic administration of D-gal induces changes that resemble natural aging in rodents, including neurodegeneration (Ho et al, 2003;Zhang et al, 2005) and cognitive dysfunction (Cui et al, 2006;Wang et al, 2013), and thus becomes a routinely used method to induce aging in rodents (Wei al., 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the evidence from a previous study in older adults with MCI and AD dementia (de Souza Silva et al, 2013), we additionally determined the association of the rs2765 SNP with hippocampus volumes. For comparison, we determined the association of ApoE ε4 genotype with regional brain volumes.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study had shown that the rs2765 SNP of the TACR3 gene was associated with right hemispheric hippocampus volume in 111 participants with MCI or AD dementia (de Souza Silva et al, 2013). This previous study had assessed hippocampus volume as a brain region with dense cholinergic innervation and a target area of cholinergic activation mediated through the medial septum in response to activation of the NK3 receptor (Schäble et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations